2013
DOI: 10.1371/journal.pone.0062700
|View full text |Cite
|
Sign up to set email alerts
|

Tibet as a Potential Domestication Center of Cultivated Barley of China

Abstract: The importance of wild barley from Qinghai-Tibet Plateau in the origin and domestication of cultivated barley has long been underestimated. Population-based phylogenetic analyses were performed to study the origin and genetic diversity of Chinese domesticated barley, and address the possibility that the Tibetan region in China was an independent center of barley domestication. Wild barley (Hordeum vulgare ssp. spontaneum) populations from Southwest Asia, Central Asia, and Tibet along with domesticated barley f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 49 publications
5
34
0
Order By: Relevance
“…vulgare) was domesticated about 10 000 years ago (Badr et al, 2000), most likely from multiple domestication centers (Morrell and Clegg, 2007;Saisho and Purugganan, 2007;Fuller et al, 2011;Ren et al, 2013). An adaptable species, barley has been of great importance also in regions where climate or soil is sub-optimal for agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…vulgare) was domesticated about 10 000 years ago (Badr et al, 2000), most likely from multiple domestication centers (Morrell and Clegg, 2007;Saisho and Purugganan, 2007;Fuller et al, 2011;Ren et al, 2013). An adaptable species, barley has been of great importance also in regions where climate or soil is sub-optimal for agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological, archaeological, cytogenetic and isozyme data revealed that wild barley on the Qinghai-Tibet Plateau is different from that in the Fertile Crescent33. Diversity array technology (DArT) data and population-based phylogenetic analyses indicated that the Tibetan Plateau and its vicinity is one of the domestication centers of cultivated barley3233.…”
mentioning
confidence: 99%
“…Morphological, archaeological, cytogenetic and isozyme data revealed that wild barley on the Qinghai-Tibet Plateau is different from that in the Fertile Crescent33. Diversity array technology (DArT) data and population-based phylogenetic analyses indicated that the Tibetan Plateau and its vicinity is one of the domestication centers of cultivated barley3233. Recent transcriptome profiling and population-based genetic diversity analysis also provided strong evidence that barley domestication may have occurred independently in geographically distinct regions3435.…”
mentioning
confidence: 99%
“…The Himalayas can be considered a region of domesticated barley diversification (Badr et al, 2000), while Tibet is a potential domestication center of cultivated barley in China (Ren et al, 2013). Due to its complex topography and diverse climate zones, soil types, regional microclimates, and habitat, the Qinghai-Tibet Plateau generates abundant diversity of genetic germplasm.…”
Section: Diversitymentioning
confidence: 99%